2018
DOI: 10.1002/eqe.3102
|View full text |Cite
|
Sign up to set email alerts
|

Introducing new design spectra derived from Italian recorded ground motions 1972 to 2017

Abstract: Summary The shape of design spectra, traditionally based on regions characterized by constant displacement, constant velocity, and constant acceleration, has been discussed from a conceptual point of view by Calvi (2018). In the same study, a formulation for the definition of the design spectra relying on four parameters was proposed. Predictive models are proposed herein to calculate these four parameters, conditional on magnitude and distance. These models were developed using a large number of recorded grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…There are different possibilities for the definition of design spectra based on S e,D,a . However, in the simplest case, the design spectrum can be determined by normalizing the assumed shape of the spectrum (eg, Eurocode 8 elastic spectrum, design spectrum proposed by Calvi et al) to the risk‐targeted design spectral acceleration S e,D,a . In this way, the entire risk‐targeted design spectrum is defined, which can be used for force‐based design in exactly the same way as, for example, the design spectrum in Eurocode 8…”
Section: Determination Of Risk‐targeted Design Seismic Actionmentioning
confidence: 99%
“…There are different possibilities for the definition of design spectra based on S e,D,a . However, in the simplest case, the design spectrum can be determined by normalizing the assumed shape of the spectrum (eg, Eurocode 8 elastic spectrum, design spectrum proposed by Calvi et al) to the risk‐targeted design spectral acceleration S e,D,a . In this way, the entire risk‐targeted design spectrum is defined, which can be used for force‐based design in exactly the same way as, for example, the design spectrum in Eurocode 8…”
Section: Determination Of Risk‐targeted Design Seismic Actionmentioning
confidence: 99%
“…The application of the appropriate conceptual correction, as discussed in this paper, may result in even more relevant effects if spectra shapes with no constant velocity regions are considered, or when the spectra are used as a basis to derive floor spectra …”
Section: Discussionmentioning
confidence: 99%
“…The second one is applied in a revised version of the capacity spectrum method , originally proposed by Freeman . In this formulation, the capacity of the structure is described by the nonlinear envelope curve resulting from some push‐over analysis; the demand is represented by a combined spectral acceleration ( S a ) spectral displacement ( S d ) shape, as shown in Figure 2 …”
Section: Inelastic Displacement Spectra In Displacement‐based Design mentioning
confidence: 99%
“…The spectral shape proposed by Calvi 1 and Calvi et al 2 is defined as a function of two points (C and D in Figure 1), identified as the longest period (T C ) at which the spectral acceleration will be at 90% of the peak spectral acceleration (S aC ) and the shortest period (T D ) at which the spectral displacement will reach 90% of the maximum spectral displacement (S dD ). The formulation is completed by the coefficient α that defines the spectral ordinates in the intermediate region (Figure 1).…”
Section: Description Of Investigated Datamentioning
confidence: 99%
“…The formulation proposed in this study defines soil amplification factors from the ratio of spectral quantities of soil deposits (soil class B or C) to quantities defined for rock-like soil (soil class A), computed using Equations ( 1)- (2). The following equations of soil amplification factors (S SaC = SaC soil /SaC rock , S SdD = SdD soil /SdD rock , S T = T soil /T rock ) have been derived from the ratios of the fitting equations (the derivation of the equations is reported in Appendix A and the parameters in Table 2 and 3):…”
Section: Definitions Of the Analytical Formulation Of Soil Amplification Factorsmentioning
confidence: 99%